Analisa Kelemahan Sistem Informasi Akuntansi Digital Dengan Menggunakan Metode PIECES Pada Bumdes Rajunohitipori Desa Rutong - Situmeang, Mis Fertyno; Patty, Meidylissa; Usemahu, Rasni Hanipa; Sandanafu, Sally (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Rutong Country Tourism Village is a digital-based tourism village in the city of Ambon. Village digitalization is an indicator and one of the criteria for a village because of the technology applied in the village. However, the application of technology should be balanced by the skills of human resources in it so that it can directly increase the income of village communities that have MSMEs. Village digitalization still needs to be developed from all aspects. This study aims to analyze and evaluate how the application of the Digital Accounting information system in the Rutong tourist village already has a digital space to promote the potential of the village based on digital sales data. The research method uses qualitative methods, namely observation, survey and interviews with PIECES analysis tools in analyzing the weaknesses of the ongoing and continuous digital Accounting Information System. Based on the results of the research, both performance, information, economy, control and service are still very lacking, so it is recommended to use the BUMDes financial report application which can accelerate input, process and output. Human resources also need to be improved by providing training on accounting basics and how to use the application. Keywords: Tourism Village, Digital Accounting Information System, Pieces